Displaced by development : confronting marginalisation and gender injustice - Mehta, Lyla (Sage, 2009)
This compilation is a rare attempt to apply gender analysis to development-induced-displacement and resettlement in the Indian context. It brings together leading scholar-activists, researchers and contributors from people's movements to critique and draw attention to the injustices perpetrated during such processes. Facing up to the need to focus specifically on how displacement and resettlement affect social groups differently with regard to axes such as gender, class, caste and tribe, the articles show that disenfranchised groups are deemed dispensable and tend to be affected the most, and that women and children among them suffer disproportionately.